Effect of Ethanol Concentration and Extraction Time with Microwave Assisted Extraction on Antioxidant Activity of Temulawak-Extract (Curcuma Xanthorrhiza.Roxb) - Septiana, Aisyah; Wuryatmo, Erminawati (Swiss German University & Perhimpunan Penggiat Pangan Fungsional dan Nutrasetikal Indonesia (P3FNI), 2022)
Temulawak (Curcuma xanthorrhiza Roxb) is commonly used as traditional medicine. This study aimed at determining the effect of ethanol concentration and of the duration of microwave-assisted extraction (MAE) on antioxidant activity of C. xanthorrhiza ethanol extract. C. xanthorrhiza rhizomes were extracted using 70%, 80% and 90% (v/v) ethanol for 5, 7 and 9 minutes. compared to control (without microwave extraction) and analyzed for curcumin content, total phenolic content (TPC), and 2,2-diphenyl-1-picrylhydrazyl (DPPH) radical scavenging capacity (RSA). Increasing the ethanol concentration from 70% to 90% as solvent and increasing the extraction time from 0 to 7 minutes at 240 watt caused an increase in curcumin content, TPC, and DPPH RSA. Curcumin, TPC, and DPPH RSA of C. xahorrhiza extract using 90% ethanol solvent for 7 minutes were the largest compared to other treatments, namely 184 mg/g, 319,5 mg/g and 71.08%; respectively.